Production of antioxidants by Marasmiellus sp. via solid substrate fermentation - Daker, M.; Abdullah, N.; Vikineswary, S.; Kuppusamy, U.R. (2009)
This study was aimed to evaluate the antioxidant properties of methanol extracts of fermented substrates optimised for antioxidant production by Marasmiellus sp. KUM 50061 mycelial biomass. Extract of fermented maize supplemented with (w/w) malt extract 4, yeast extract 4 and rice bran 4 exhibited the highest 1,1diphenyl-2-picrylhydrazyl radical scavenging ability. The effective concentration of extract to scavenge 50 radicals was 1.875 mg mL-1. This formulation was chosen as the optimum substrate for antioxidant production by Marasmiellus sp. KUM 50061 mycelial biomass. The thiobarbituric acid reactive substance (TBARS) assay showed that the effective concentration to inhibit lipid peroxidation of buffered egg yolk by 50 was 6.00 mg mL-1. Total phenolics amounted to 31.41Â±1.56 mg GAE g-1 extract as measured by the Folin-Ciocalteau method.